2015
DOI: 10.1111/codi.12810
|View full text |Cite
|
Sign up to set email alerts
|

What role do bacteria play in persisting fistula formation in idiopathic and Crohn's anal fistula?

Abstract: Anal fistula tracts generally do not harbour high levels of mucosa-associated microbiota. Crohn's anal fistulas do not seem to harbour specific bacteria. Alternative explanations for the persistence of anal fistula are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 19 publications
1
33
3
1
Order By: Relevance
“…It is therefore of relevance to point out microbiological differences that may occur between the two diseases. A recent study investigated the potential presence of bacteria in Crohn's and idiopathic anal fistulas using FISH and scanning electron microscopy ( n = 51) . Interestingly, the study indicated that Crohn's fistulas do not harbour specific bacteria, which is in contrast to our findings.…”
Section: Discussioncontrasting
confidence: 99%
“…It is therefore of relevance to point out microbiological differences that may occur between the two diseases. A recent study investigated the potential presence of bacteria in Crohn's and idiopathic anal fistulas using FISH and scanning electron microscopy ( n = 51) . Interestingly, the study indicated that Crohn's fistulas do not harbour specific bacteria, which is in contrast to our findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, it seems unlikely that bacterial infection plays a major role in persistence of fistula after surgery. These results were recently confirmed by Tozer et al [4]. …”
Section: Introductionsupporting
confidence: 81%
“…Two groups have tried to address these issues and to understand the microbiota within the perianal fistula track. In one study, 32 fistula tracks (14 Crohn's, 18 idiopathic) were sampled using fluorescent in situ hybridisation which allows identification and quantification of mucosa‐associated bacteria held within the mucus layer of the luminal surface of the fistula track . No luminal bacteria were found despite the additional use of several techniques (including “no wash” collection techniques and scanning electron microscopy (SEM)) to ensure technical causes were not responsible for the paucity of bacteria seen.…”
Section: Methodsmentioning
confidence: 99%